ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI ARITMATIKA SOSIAL DENGAN TAHAPAN NEWMAN - Fina Rosmiati; Rippi Maya (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
Sosial arithmetic is one of the subject matter of mathematics which includes, among others, buying and selling, profit and loss. Students need to understand this material well in order to be able to apply it in daily life to the fullest. This research is a qualitative descriptive study that aims to analyze students’ mistakes in solving social aritmetic problems, based on Newman’s stages. This research was conducted at SMP Negeri 55 Bandung with the subject as many as 23 students of VIII Grade. The student test results data are in the form of 5 questions, then the errors are analyzed based on the Newman stages and described for each item. The results showed that based on Newman’s stage, the type of error that most students made was process skill error, while the type of error that students made the least amount of error was reading error.